Knowledge and Practices Regarding Self-Management of Minor Ailments among Pregnant Mothers - Samara, Suduweli Koonge Sashanika Nishadi; Mohamed, Fathima Farhana Habeeb; Madushanka, Kalanchi Mahadurage Shalitha; Gnanaselvam, Kisokanth (Journal of Maternal and Child Health, 2020)
Background: